2023
DOI: 10.1002/tafs.10418
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Muskellunge catch‐and‐release mortality at elevated summer water temperature

Abstract: Angling for Muskellunge Esox masquinongy has become widespread and increasingly popular. Management strategies for Muskellunge include high minimum harvest lengths (>1016mm), closed seasons, and catch‐and‐release regulations. Due to these strategies and angler behaviors, up to 97% of Muskellunge caught are released, and anglers assume these fish survive to be caught again in the future. Previous research on catch‐and‐release mortality for Muskellunge has suggested relatively low mortality rates (0%‐5%). How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 85 publications
(94 reference statements)
0
0
0
Order By: Relevance
“…This elevated activity rate may be a result of fish searching for suitable habitat, foraging on pelagic prey or from conspecific interactions, such as competition for homeranges/foraging locations, predation or mating. We also found that muskellunge are unable to locate thermal refuges in water cooler than 26°C, which can lead to higher incidental mortality following an angling experience (Booth et al., 2023). Managers of reservoirs should consider adding benthic structure or reducing stocking densities over time so prey can reduce in number (Bolding et al., 2004), and the effect of habitat addition on movement rates can be quantified in future studies.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…This elevated activity rate may be a result of fish searching for suitable habitat, foraging on pelagic prey or from conspecific interactions, such as competition for homeranges/foraging locations, predation or mating. We also found that muskellunge are unable to locate thermal refuges in water cooler than 26°C, which can lead to higher incidental mortality following an angling experience (Booth et al., 2023). Managers of reservoirs should consider adding benthic structure or reducing stocking densities over time so prey can reduce in number (Bolding et al., 2004), and the effect of habitat addition on movement rates can be quantified in future studies.…”
Section: Resultsmentioning
confidence: 78%
“…Of concern, however, is how muskellunge use water temperatures 26°C and above in the summer. The 26°C temperature represents a critical threshold associated with higher incidental mortality following angling of muskellunge (Bauerlien, 2022; Beggs et al., 1980; Booth et al., 2023). This mortality is thought to be associated with greater physiological stress, which leads to reduced ability to recover and survive an angling experience (Booth et al., 2023).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations